Perancangan Gedung Studio Musik dengan Konsep Modular di Limboto - Ahlando Beu; M Fauzhan Algiffari; Frans Mitran Ajami (Politeknik Kebangsaan, 2025)
The rapid growth of the Indonesian music industry demands efficient and functional creative spaces. However, limited land and high conventional construction costs pose significant challenges. This research proposes a modular concept as a flexible, efficient, and sustainable design solution for a music studio. This approach addresses the issues of rigid conventional designs that are difficult to adapt to changing functions. The study uses A-WERE Studio in Gorontalo as a case study, aiming to design a music studio that not only meets acoustic standards but is also adaptable to future needs. The research and design findings show that the modular concept, with a basic 4m x 4m module, proves effective in addressing challenges of limited land and construction costs. This design allows for expansion and function changes without extensive renovation. Acoustic quality is a primary focus, with the implementation of features like double walls, a floating floor, and acoustic panels to ensure that reverberation time (RT60) standards are met. A clear zoning of spaces separates the production, support, and service areas for efficient circulation. The building's structure uses galvanized light steel frames and sandwich panels, which support a fast and environmentally friendly dry construction system. Sustainability is also emphasized through the use of recyclable prefabricated materials, a natural ventilation system, and efficient lighting. The resulting design is a professional music studio that is not only functional and aesthetically pleasing but also flexible, efficient, and adaptable to future needs, making it a benchmark for the development of creative spaces in Indonesia.